2017
DOI: 10.1002/2017je005336
|View full text |Cite
|
Sign up to set email alerts
|

On the Origins of Mars' Exospheric Nonthermal Oxygen Component as Observed by MAVEN and Modeled by HELIOSARES

Abstract: The first measurements of the emission brightness of the oxygen atomic exosphere by Mars Atmosphere and Volatile EvolutioN (MAVEN) mission have clearly shown that it is composed of a thermal component produced by the extension of the upper atmosphere and of a nonthermal component. Modeling these measurements allows us to constrain the origins of the exospheric O and, as a consequence, to estimate Mars' present oxygen escape rate. We here propose an analysis of three periods of MAVEN observations based on a set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 32 publications
(47 citation statements)
references
References 86 publications
0
47
0
Order By: Relevance
“…According to Leblanc et al (), the precipitating ion flux is highly dependent on the solar zenith angle, on the position of the most intense crustal magnetic field structures, and on the orientation of the convective electric field. Indeed, Hara, Luhmann, Leblanc, Curry, Seki, et al () showed that the intensity of the precipitating ion flux peaked on the hemisphere toward which the E SW field pointed (the −E SW hemisphere).…”
Section: Resultsmentioning
confidence: 99%
“…According to Leblanc et al (), the precipitating ion flux is highly dependent on the solar zenith angle, on the position of the most intense crustal magnetic field structures, and on the orientation of the convective electric field. Indeed, Hara, Luhmann, Leblanc, Curry, Seki, et al () showed that the intensity of the precipitating ion flux peaked on the hemisphere toward which the E SW field pointed (the −E SW hemisphere).…”
Section: Resultsmentioning
confidence: 99%
“…All these reactions are indeed usually considered as marginally contributing to the atmospheric escape compared to O 2 + dissociative recombination. We discussed this issue in Leblanc et al (2017) showing that at least a factor 3 difference can be retrieved by using the same cross sections. This is roughly 6 times smaller than our present estimate.…”
Section: Application To Egmmentioning
confidence: 99%
“…We also determine how the exosphere could be shaped by the sputtered atmospheric Leblanc et al, 2017) developed to describe Mars's exosphere at any Martian season and solar activity. We also determine how the exosphere could be shaped by the sputtered atmospheric Leblanc et al, 2017) developed to describe Mars's exosphere at any Martian season and solar activity.…”
Section: Introductionmentioning
confidence: 99%
“…A detailed description of the LatHyS model can be found in Modolo et al (, and references therein). The description of the neutral and ionospheric Martian environment that affect, among other things, the mass‐loading conditions of the SW is derived making use of the 3‐D LMD‐GCM (Chaufray et al, , ; González‐Galindo et al, ) and the 3‐D EGM (Leblanc, Chaufray, et al, ; Leblanc, Leclercq, et al, ).…”
Section: Maven Instruments and Lathys Codementioning
confidence: 99%